Executives' Characteristics and Strategic Choice - Islam, Sigma (2019)
This study is conducted to addcontributions to the literature related to executive characteristics and strategic choice of the organizations. The upper echelons theory proposed by Hambrick and Mason (1984) is the primary basis of this research. To achieve the objective of the dissertation that is how executives’ characteristics like gender, age, education, functional background, tenure, experience, nationality, compensation and socioeconomic profile influence organizational strategic decision making 20 executives working in various organizations of Bangladesh have been interviewed over the telephone. However, the questionnaire was provided to the respondents through email before the interview. The questionnaire has been developed by following the work done by Dearborn and Simon (1958) and Walsh (1988). The quantitative information about the characteristics of executives is included in the descriptive statistics part which is then followed by the qualitative analysis of responses provided by the respondents to ranking task and questions related to the case study which is adapted from the case developed by Ebster, and Khalil, (2018). From the analysis of the responses of the participants, it has been found that executives’ level of education and the functional track is positively related to innovative decision making. Similarly, executives’ experiences of working in various organizations positively influence their innovative decision making and male executives tend to take more risk compared to their female counterparts. This dissertation, however, could not find any significant association between executives’ age, tenure, compensation, and socioeconomic profiles and their strategic choice. As all of the executives’ nationality is Bangladeshi, it was not possible to identify the differences in the decision-making of executives based on nationality. In the last part of the dissertation, some future research directions are provided.